Pengaruh Sistem Informasi Perpajakan Terhadap Kepatuhan Wajib Pajak dan Penerimaan Pajak di Kantor Pelayanan Pajak Badan dan Orang Asing Satu Menurut Wajib Pajak - Alief Ramdan (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
This study aims to determine the relationship and influence of adequate taxation information system on taxpayer compliance and tax revenue. This research was conducted in the Office of Tax Service of Foreign Body and Person (KPP Badora) 1, in May 2006 with sample 115 Taxpayer Agency taken at random from 910 taxpayers or +/- 2% of the population. Instrument for collecting data of taxation information system (Y1) and taxpayer compliance (X1) is questionnaire of Likert scale model while tax revenue data (Y2) is secondary data obtained directly from KPP Badora 1.The analysis was done quantitatively with two statistical analysis techniques to be used in this study, namely regression analysis and Mann-Whitney difference test. Regression analysis techniques used to determine and predict the effect of tax information systems on taxpayer compliance and tax revenue. While the mean difference test of Mann-Whitney is used to detect whether there is a difference between the tax revenue level of KPP Badora 1 between before the use of computerized system and after use of the system. Interpretation of data analysis results using significance α = 5%.Regression analysis results show that there is a significant relationship between the application of tax information systems with taxpayer compliance of 0.653. While the big influence of the application of tax information system on taxpayer compliance is equal to 42.6%. Linear regression equation ŷ = 25.231 + 0.538 X. Mann-Whitney test results show that there is no significant difference between tax revenues before and after the implementation of tax information system which means that the application of tax information system does not affect significantly to tax revenue.